How to solve this equation over real numbers with parameter $p \in \Bbb R$? $$(1 - p)(\left\lvert x + 2 \right\rvert + \left\lvert x \right\rvert) = 4 - 3p$$

I know how to solve absolute value equations without parameter.


We have $$|x|+|x+2|=\frac{4-3p}{1-p}\tag1$$

Case 1 : For $x\gt 0$, $$(1)\iff x+(x+2)=\frac{4-3p}{1-p}\iff x=\frac{2-p}{2(1-p)}$$ Here, $\frac{2-p}{2(1-p)}\gt 0\iff p\lt 1\quad\text{or}\quad p\gt 2$.

Case 2 : For $-2\lt x\le 0$, $$(1)\iff -x+(x+2)=\frac{4-3p}{1-p}\iff p=2$$

Case 3 : For $x\le -2$, $$(1)\iff -x-(x+2)=\frac{4-3p}{1-p}\iff x=\frac{6-5p}{2(p-1)}$$ Here, $\frac{6-5p}{2(p-1)}\le -2\iff p\lt 1\quad\text{or}\quad p\ge 2$.

So, the answer is the followings :

  • For $p\lt 1\ \text{or}\ p\gt 2$, $x=\frac{2-p}{2(1-p)},\frac{6-5p}{2(p-1)}$.

  • For $p=2$, $-2\le x\le 0$.

  • For $1\le p\lt 2$, there is no such $x$.

  • 1
    $\begingroup$ Well detailed answer, nice job! +1 $\endgroup$ – Nicolas Aug 9 '15 at 19:04

I am sensing a homework question here :P Anyways.

Just remember,

|x| = x , when x>=0 &

|x| = -x , when x<0

So , just change the equation accordingly to these cases and solve it.

For x<0 , above equation becomes

(1-p)(-x-2-x) = (4 - 3p) hence, it becomes

(1-p)(-2x - 2) = (4 - 3p)

Now , for the case x>=0 , I am leaving it to you as homework for trying it out yourself. I hope this helps.


HINT....use the definition of $|x|$ in the form $$|x|= \begin{cases} x &x\geq 0 \\-x & x<0 \end{cases}$$, So that you can split the equation into three separate cases. So, for example, when $x\geq 0$, the equation becomes $$(1-p)(2x+2)=4-3p$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.